Distribución de huevos, larvas y juveniles de peces en los sectores surbonaerenses, patagónico y fueguino del mar epicontinental argentino, en relación con las condiciones ambientales, en Noviembre 1973-Enero 1974 - Ciechomski, Juana D.; Cassia, María C.; Weiss, Graciela (Ecosur, 2025)
The prescnt paper deais with the rcsults of the studies on the distribution and abundance of the eggs, larvae and postlarvae of different species of fish in the plankton off the coasts of Argentina between the latitudes between 39°46’S y 55°02’S. The material was obtainod during the cruisc of the polish highseas research vessel “Profesor Siedlecki” perfomed during November 1973 - January 1974. The surveys covcred the shelf, in some cases including vvaters of the continental slope. Areas of the distribution of different eomponents of ichthyoplankton are described. The relation is analized between the distribution of ichthyoplankton and the following ambiental factors: temperature, salinity, some nutrients, depth, geographical latitude and biomass of largor zooplanktonicorganisms. On this basis three ecological groups of fish post-larvae in the studied area are destinguished; 1) of lower latitudes, shallow waters and higher temperatures, 2) of higher latitudes, lower temperature and mostly bigger depths, 3) of habitat in largor range of latitudes, temperatures and depths. It was stated that to lower densities of zooplanktonic organisms correspond larger densities of fish eggs. Higher concentrations of fish larvae and postlarvae are related to lower and modérate valúes of the biomass of these organisms.